Antidiabetic and antihyperlipidemic effects of kodo millet-supplemented Flatbreads in streptozotocin induced diabetic Wistar rats - Tariq Khan; Muzamil Liakat Mir; ZR Azaz Ahmad Azad; GG Hammad A Shadab; Nazia Tabassum (Nutrition and Health, 2026)
Background Diabetes mellitus is a global metabolic disorder characterised by hyperglycaemia, dyslipidaemia, oxidative stress and hepatic dysfunction. Functional foods such as millets are increasingly recognised for their therapeutic potential in managing metabolic diseases. Aim This study aimed to investigate the antidiabetic, antihyperlipidaemic, hepatoprotective and antioxidant effects of flatbreads enriched with graded levels of kodo millet (KM, 25–100%) in streptozotocin (STZ)-induced diabetic rats. Methods Male Wistar rats with STZ-induced diabetes were fed KM-based flatbreads containing varying proportions (25–100%) for 28 days. Biochemical markers, including fasting blood glucose (FBG), serum insulin (SI), HbA1c, liver function enzymes (alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP)), lipid profile (total cholesterol, triglyceride, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C)), oxidative stress (lipid peroxidation) and antioxidant parameters (reduced glutathione (GSH), superoxide dismutase (SOD), CAT), were evaluated. Additionally, in vitro inhibitory activities against α-amylase and α-glucosidase were assessed. Summary The 75% KM formulation (KM75) produced the most notable therapeutic benefits. KM75 significantly reduced FBG (43.08%) and HbA1c (52.33%) levels ( p < 0.001) and increased SI levels (50.4%) ( p < 0.001). Liver enzyme activity decreased markedly (ALT:41.99%, AST:42.63%, ALP:36.95%), confirming hepatoprotection. Lipid metabolism improved, with a decline in total cholesterol (30.54%), triglycerides (43.33%), LDL-C (49.55%) and a remarkable increase in HDL-C (123.36%) ( p < 0.001). Antioxidant defence markers (GSH, SOD, CAT) increased by ∼25%, while lipid peroxidation was reduced by 34.01%. Both KM75 and KM100 showed strong α-amylase and α-glucosidase inhibitory activities, although no further benefits were observed at 100% inclusion, suggesting an optimal therapeutic level at 75%. These findings highlighted 75% KM supplementation as a promising dietary intervention for diabetes management and its associated complications.